Decentralization and the Fate of Minorities - Kjetil Bjorvatn; Alexander W. Cappelen (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper analyses the welfare effects of a change from centralized to decentralized political authority. The potential disadvantage with decentralization in our model is that local dominant groups with rather extreme preferences may win the vote and implement policies that harm the well-being of local minorities. When the national median voter represents a moderate position, centralization can be seen as a way of protecting the interests of local minorities. Our main result is that the centralized solution may welfare dominate decentralization even in the absence of scale economics and interregional spillovers. We also demonstrate that increased segregation, increased mobility, and increased heterogeneity in preferences, factors that are normally considered to be arguments in favor of decentralization, may reduce the attractiveness of the decentralized solution from a welfare perspective. Finally, we show that when the national median voter is an extreme type, decentralization may represent a way of protecting local minority interests.
Keywords: 330